COMPETITIVE ADVANTAGES ENTERPRISES IN KOOPERATION RELATIONS - O. Mikitiuk (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
Formation of new approaches to the definition of competitive advantage requires different ways to implement them according to market conditions. These paths can be cooperative relations entities that are implemented in the competitive advantage of enterprises in the new stage of development of a competitive society. The result of the interaction of small businesses with industrial and economic structures is the formation and development of such forms of cooperation entities as subcontracting, franchising, leasing, venture finance. The content of these forms is to integrate (interlacing) of the functional areas of business including production of functional form is subcontracting relationships, forms of supply – franchising, industrial and financial shape – leasing as a form of innovative functional integration relations is venture financing.